2013
DOI: 10.1186/1471-2458-13-687
|View full text |Cite
|
Sign up to set email alerts
|

pH1N1 - a comparative analysis of public health responses in Ontario to the influenza outbreak, public health and primary care: lessons learned and policy suggestions

Abstract: BackgroundOntario’s 36 Public Health Units (PHUs) were responsible for implementing the H1N1 Pandemic Influenza Plans (PIPs) to address the first pandemic influenza virus in over 40 years. It was the first under conditions which permitted mass immunization. This is therefore the first opportunity to learn and document what worked well, and did not work well, in Ontario’s response to pH1N1, and to make recommendations based on experience.MethodsOur objectives were to: describe the PIP models, obtain perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 4 publications
0
40
0
Order By: Relevance
“…The reviews covered national and international responses to the 2009 A(H1N1) influenza pandemic (n = 8), [21][22][23][24][25][26][27][28] terrorist bombing incidents (n = 5), [29][30][31][32][33] industrial explosions (n = 6), [34][35][36][37][38][39] hurricanes (n = 2), 40 , 41 chemical contamination of drinking water (n = 1), 42 a heat wave (n = 1), 43 and largescale flooding (n = 1) (see Table 1). 44…”
Section: Results Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The reviews covered national and international responses to the 2009 A(H1N1) influenza pandemic (n = 8), [21][22][23][24][25][26][27][28] terrorist bombing incidents (n = 5), [29][30][31][32][33] industrial explosions (n = 6), [34][35][36][37][38][39] hurricanes (n = 2), 40 , 41 chemical contamination of drinking water (n = 1), 42 a heat wave (n = 1), 43 and largescale flooding (n = 1) (see Table 1). 44…”
Section: Results Overviewmentioning
confidence: 99%
“…Validity boosting measures most frequently reported in the 24 reviews included spending adequate time to observe the setting, people, and incident documentation; sampling a diverse range of views; using multiple sources of data collection; and utilizing multiple perspectives during the analysis 21 44 However, these techniques were generally reported in brief, with few reviews fully meeting all 4 basic validity dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the 'openness and inclusiveness in institutional processes and constructive interactions' (Schmidt, 2013, p. 8) are particularly important. A survey conducted in Canada in the aftermath of the H1N1 pandemic revealed that -although there was not any single best model of how to handle the crisis -the comprehensive planning, the involvement of multiple stakeholders and communication (both among the official bodies as well as with the general public) were crucial to address the crisis successfully (Masotti et al, 2013). Similarly, the literature on disaster management stresses also the inclusion of various stakeholders and both internal and external distribution of information as factors crucial for success (Harrald, 2006;Moe and Pathranarakul, 2006;Fitzgerald et al, 2012;Schemann et al, 2012).…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…At the beginning of the epidemic, it was common for health professionals and the population to face deficiency or an excess of information about the problem, coming from the most varied institutions and through the most diverse channels. In general, these studies show that such plans must be as operational as possible, focusing on what is especially necessary to be done in the health service that directly impacts the quality of care offered, with the greatest possible safety for users and professionals [14][15][16]19 .…”
Section: Planning Of Communication Actions and Strategiesmentioning
confidence: 99%
“…Some studies, especially those from fragmented systems in developed countries [14][15][16] , show that healthcare workers can receive contradictory or redundant messages from different sources: their own institutions, local and national health authorities, media and scientific literature.…”
Section: Planning Of Communication Actions and Strategiesmentioning
confidence: 99%